Monthly resolved coral barium isotopes record increased riverine inputs during the South Asian summer monsoon. (15th July 2022) - Yu, Yang; Hathorne, Ed; Siebert, Christopher; Felis, Thomas; Rajendran, C.P.; Frank, Martin
Abstract: We present a monthly resolved stable Ba isotope record (δ 138 Bacoral ) of a young fossil coral ( Porites ) from the eastern side of the Andaman Islands (NE Indian Ocean), which grew prior to the 19th century. This δ 138 Bacoral record complements 19-years of monthly resolved Ba/Cacoral, Sr/Cacoral, U/Cacoral, δ 18 Ocoral and δ 13 Ccoral data from the same colony that can serve as a baseline of environmental variability before the industrialised era. The δ 138 Bacoral record exhibits small but significant seasonal variability ranging from 0.16 to 0.27 ± 0.03‰ over two continuous annual cycles. The δ 138 Bacoral signature is generally low during the South Asian summer monsoon (SAM, June-September) and post-SAM seasons (October-January), which are characterised by high Ba/Cacoral and more depleted δ 18 OSW values. We suggest that Ba desorption from suspended fluvial sediments followed by lateral advection are the main causes of the low δ 138 Bacoral and elevated Ba/Cacoral values during the SAM and post-SAM. However, this promising Ba proxy behaviour is interrupted by pronounced spikes of low δ 138 Bacoral and high Ba/Cacoral signatures observed during the pre-SAM season (February-May) throughout the 19-year record. Possible explanations for these spikes observed during dry seasons are (1) Ba enrichment associated with decreased mixed layer depth or (2) Ba release from sediments trapped by local fringing mangroves. Surface seawater from the coral site sampled over an annual cycle exhibits a wide range of dissolved δ 138 BaSW and [Ba]SW values, with significantly lowered δ 138 BaSW of 0.29 ± 0.04‰ and high [Ba]SW of 66.03 nmol/kg during the SAM, which is broadly consistent with the coral skeletal signals. Our results establish a clear link between monsoon-driven freshening events and Ba isotope variability of surface waters and assess the utility of coral skeletal Ba isotopes to trace riverine inputs into tropical coastal oceans.